2018
DOI: 10.4149/bll_2018_067
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus and thyroid disease: a two-sided analysis

Abstract: Patients with T2DM showed to have higher prevalence of AITD and primary hypothyroidism. We did not find higher prevalence of T2DM in patients with thyroid diseases (Tab. 3, Ref. 29).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
4
12
0
2
Order By: Relevance
“…As can be seen from Table 2, the prevalence of thyroid antibodies positive in the T2DM combined NAFLD group was significantly higher than that in the T2DM group alone, and TPOAb positive are more than TGAb-positive patients, the prevalence of TPOAb-positive was significantly different between the two groups. Other studies have also shown that elevated TPOAb is predominant in patients with positive thyroid autoimmunity whether in patients with T2DM alone and NAFLD alone, 9,25,29 consistent with our findings. This study found that the prevalence of thyroid autoimmunity in patients with T2DM complicated with NAFLD was 6.6%, which was not statistically significant compared with T 2 DM alone group (3.7%), but it also showed a significant upward trend.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As can be seen from Table 2, the prevalence of thyroid antibodies positive in the T2DM combined NAFLD group was significantly higher than that in the T2DM group alone, and TPOAb positive are more than TGAb-positive patients, the prevalence of TPOAb-positive was significantly different between the two groups. Other studies have also shown that elevated TPOAb is predominant in patients with positive thyroid autoimmunity whether in patients with T2DM alone and NAFLD alone, 9,25,29 consistent with our findings. This study found that the prevalence of thyroid autoimmunity in patients with T2DM complicated with NAFLD was 6.6%, which was not statistically significant compared with T 2 DM alone group (3.7%), but it also showed a significant upward trend.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have found that the prevalence of thyroid dysfunction is significantly higher in patients with T2DM than in the normal population. 18,25 In patients with T2DM, hypothyroidism is the most common type of thyroid dysfunction, with the incidence ranging from 18.3% to 45.2%. 18,25,26 The differences in the above results may be related to different detection methods, different races, and sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are supported by those of Hage et al, who reported that diabetes and thyroid disorders, both of which involve endocrine system dysfunction, tended to coexist in patients, and of Sotak et al, who stated that patients with type 2 diabetes had a higher prevalence of hyperthyroidism and autoimmune thyroid disease. Our and previous findings thus validate the temporal relationship between type 2 diabetes and thyroid disease 42,43 .…”
Section: Discussionsupporting
confidence: 89%
“…There was also no association between hyperthyroidism and DM development reported in the contemporary literature. [27] In a study that followed a total of 8452 pre-diabetic patients from the Netherlands for 7.9 years, the risk of DM occurrence was lower (0.96) in subjects with higher serum-free T4 level compared with the normal control. [21] In addition, hypothyroidism patients possessed a higher risk (HR: 1.13–1.75) of developing DM than the controls from the above study and in an Israel study of around 60,000 patients.…”
Section: Discussionmentioning
confidence: 99%